CAE simulation study on the effects of gate types and gate positions for the application of moulding of polymer base micro fluidic chip - Low, Yi Sheng. (2011)
Due to the high difficulty in meeting the stringent requirement for precision, injection molding is still not widely used for the fabrication of microfluidic chip. This paper aims to investigate the effects of gate design and gate position have on the mold result. The objective is to produce a flat and precise microfluidic chip with minimal defects through the optimization of gate design and gate position. For the purpose of this study, two typical sizes of microfluidic chips (25X75mm and 50X75mm) are chosen. The polymer material used in this study was polycarbonate (PC) Lexan 121R (SABIC Innovative Plastics B.V.). Actual experiment of mold process is time consuming and expensive to conduct[1]. Hence, for this study, the molding process is simulated and optimized with CAE software Autodesk Moldflow in computer. Various gate positions and gate types are tested on the two sizes of microfluidic chip and critical results such as fill time and pressure at end of view are reviewed and investigated. This study shows that it is important to find a balance between the effect of flow direction of injection material and the distribution of pressure within the part as demonstrated in the gate position experiment. It is also concluded that using a wider fan gate will produced part with less warpage as a result of decrease in pressure difference. Using a wider fan gate also solve the problem with flow mark defect.